Antioxidant and antifatigue effect of a standardized fraction (HemoHIM) from Angelica gigas, Cnidium officinale, and Paeonia lactiflora. (1st January 2021) - Kwon, Da-Ae; Kim, Yong Sang; Kim, Seul-Ki; Baek, Sin Hwa; Kim, Hyun Kyu; Lee, Hak Sung
Abstract: Context: HemoHIM is an herbal preparation containing Angelica gigas Nakai (Apiaceae), Cnidium officinale Makino (Umbelliferae), and Paeonia lactiflora Pallas (Paeoniaceae) developed for immune regulation. To date, studies on the antifatigue effects of HemoHIM have not been conducted. Objective: The antifatigue effects of HemoHIM using models of citrinin and exercise-induced chronic fatigue syndrome were investigated. Materials and methods: Citrinin-induced L6 skeletal muscle cells were treated with HemoHIM (125, 250, and 500 μg/mL). The antioxidant factors were analysed. ICR mice were divided into four groups (n = 10): control, HemoHIM 250, 500 mg/kg, and creatine 300 mg/kg, respectively. Mice were orally administered HemoHIM or creatine for three weeks; during this time, both rotarod test and forced swimming test (FST) were conducted. The latency time was investigated and antioxidant, antifatigue factors were analysed. Results: HemoHIM significantly restored reduced antioxidant enzymes (SOD, CAT, Txn, GPx, GSr, and GCLC in HemoHIM 500 μg/mL) compared to the citrinin group in L6 cells. In vivo, HemoHIM significantly improved the latency time (FST; 279.88 ± 50.32 sec, rotarod test; 552.35 ± 23.50 sec in HemoHIM 500 mg/kg). Moreover, the FST-induced reduction in glucose and glutathione significantly increased by 3-fold (HemoHIM 500 mg/kg) and increase in LDH and MDA were significantly inhibited by 1.6, 2.1-fold in the HemoHIM 500 mg/kg compared to the control group.